Analysis and Redesign of Water network & Design of Wastewater network for Kaferdan village - Abdallah Bzoor; Kefah Ali; Mohammed Abo Abed (My University, 2017)
We adopted in graduated project koferdan town that follow to Jenin governorate and its area is    (7328 dunms) and population(6399 person) for study the water and wastewater situation and develop water and waste water networks for 30 years later. As we headed to koferdan Municipal and water services Council for Villages Jenins west, We got the data that necessary for this study such as: countor lines, water distribution network ,wastewater network (if exist), koferdan map and transportation network. We will enter this data to WATER CAD sofeware for water network and SEWER CAD software for wastewater  network  and will do check on the networks if it has any problem in the networks . Then , we will develop and improvement the networks by we will do new design for them, in wich this design must agree with our aim within limited specification for some of the variable suchas: velocity of water in all pipes , the pressure in the pipes and the diameter of pipes. And was proposed the location for Wastewater treatment plant  for treated the wastewater generated from the twon.

, (7328 ) (6399 ) , , 30 .  , : () ( ) .  , ( ) , .  , .  .
Analysis and Redesign of Water network & Design of Wastewater network for Kaferdan village